Pharmacokinetic tools for the dose adjustment of ciclosporin in haematopoietic stem cell transplant patients. (October 2014) - Woillard, Jean‐Baptiste; Lebreton, Vincent; Neely, Michael; Turlure, Pascal; Girault, Stéphane; Debord, Jean; Marquet, Pierre; Saint‐Marcoux, Franck
<x xml:space="preserve">Abstract</x> Aims Ciclosporin A (CsA) is used in the prophylaxis and treatment of acute and chronic graft vs. host disease after haematopoietic stem cell (HSCT) transplantation. Our objective was to build and compare three independent Bayesian estimators of CsA area under the curve (AUC) using a limited sampling strategy (LSS), to assist in dose adjustment. Methods The Bayesian estimators were developed using in parallel: two independent parametric modelling approaches (nonmem® and iterative two stage (ITS) Bayesian modelling) and the non‐parametric adaptive grid method (Pmetrics®). Seventy‐two full pharmacokinetic profiles (at pre‐dose and 0.33, 0.66, 1, 2, 3, 4, 6, 8 and 12h after dosing) collected from 40 HSCT patients given CsA were used to build the pharmacokinetic models, while 15 other profiles (n = 7) were kept for validation. For each Bayesian estimator, AUCs estimated using the full profiles were compared with AUCs estimated using three samples. Results The pharmacokinetic profiles were well fitted using a two compartment model with first order elimination, combined with a gamma function for the absorption phase with ITS and Pmetrics or an Erlang distribution with nonmem. The derived Bayesian estimators based on a C0‐C1 h‐C4 h sampling schedule (best LSS) accurately estimated CsA AUC(0, 12 h) in the validation group (n = 15; nonmem: bias (mean ± SD)/RMSE 2.05% ± 13.31%/13.02%; ITS: 4.61% ± 10.56%/11.20%; Pmetrics: 0.30% ± 10.12%/10.47%). The dose chosen confronting the three results led to a pertinent dose proposal. Conclusions The developed Bayesian estimators were all able to predict ciclosporin AUC(0, 12 h) in HSCT patients using only three blood with minimal bias and may be combined to increase the reliability of CsA dose adjustment in routine.